Lexical Bundles in Reading Passages of English Textbook for Senior High School: A Comparative Study Between Three Textbooks of Different Grades - Ritanti Lasmita; Alamsyah Harahap; Safnil Arsyad (Edu-Ling: Journal of English Education and Linguistics, 2023)
This study discusses lexical bundles in reading passages in English textbooks for senior high school. This study has two objectives, the first is to find out lexical bundles three-word and four-word are found in reading passages of English Textbook for senior high school for X, XI, and XII grade. Second, To find of lexical Category types found in reading passages of English Textbook for senior high school entitled ”Bahasa Inggris” for X, XI, and XII grade. In addition, this study used theory from Biber. According to Biber, the categories of lexical bundles are noun phrase, verb phrase and prepositional phrase. This study uses a quantitative descriptive method used reading passages in an English textbook for senior high school entitled "Bahasa Inggris". Data collection in this study was assisted by Antconc software to determine lexical bundles and analyze lexical bundles according the category of lexical bundles. From the results of the study there were 146 lexical bundles in X grade, 203 lexical bundles in XI grade, and 199 lexical bundles in XII grade. Then, 299 categories of lexical bundles noun phrases, 159 verb phrases, and 91 lexical bundles preposition phrases. Lexical bundles three-word and four-word are found in reading passages in English textbooks. Then, three-word lexical bundles have the highest occurrence rate. In addition, the noun phrase category has a level of occurrence that is often used in reading passages in English textbooks for senior high school.